2018
DOI: 10.5897/ajfs2017.1662
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition, physical characteristics and mineral content of fruit, pulp and seeds of Parinari curatellifolia (Maula) from Central Malawi

Abstract: In this study, proximate composition, physical characteristics and mineral content of fruit, pulp and seeds of Parinari curatellifolia (Maula) fruits from Bunda forests in Central Malawi were determined. Proximate composition included crude protein, crude fat and crude fiber, while physical characteristics included mass, length, thickness of whole fruit and kernels and minerals included potassium, magnesium, manganese, copper, zinc, iron and phosphorus. Total carbohydrate contents were also determined. All the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The addition of water during dough development could have also caused the protein content to decrease. Chatepa et al [55] reported protein content of 4.17 and 3.4% for fresh peels and pulp of P. curatellifolia fruit, respectively. Similar results of a decrease in protein content of biscuits added with orange peels powder were reported by Rani et al [56].…”
Section: Nutritional Composition Of Biscuitsmentioning
confidence: 99%
“…The addition of water during dough development could have also caused the protein content to decrease. Chatepa et al [55] reported protein content of 4.17 and 3.4% for fresh peels and pulp of P. curatellifolia fruit, respectively. Similar results of a decrease in protein content of biscuits added with orange peels powder were reported by Rani et al [56].…”
Section: Nutritional Composition Of Biscuitsmentioning
confidence: 99%
“…The Mean values and standard deviations of each waste were calculated using Microsoft excel. The result was tabulated as mean ± standard deviation 20 .…”
Section: Determination Of Fixed Carbonmentioning
confidence: 99%